Pakistan’s Strategy during COVID-19 Pandemic - Faisal, Muhammad; Latif, Ijaz (Journal of Public Policy Practitioners, 2024)
The COVID-19 pandemic emerged in December 2019. The virus affected every domain of human life across the world. In particular, economy is considered to be the most affected by COVID-19 pandemic. Most of the nation-states are still experiencing socio-economic consequences. Pakistan is also not an exceptional case in this context since the COVID-19 pandemic affected its economy as well. The country is still experiencing economic depression. Therefore, the current study examined the strategy employed by Pakistani government during COVID-19 pandemic. Moreover, the study also analyzed how government used its resources to feed the population. This research concluded that the government needs a vigilant long term policy framework to stabilize the worsening economic conditions of Pakistan.